Synthesis and characterization of novel pyrazolone derivatives - Marzouk, Magda Ismail; Sayed, Galal Hosni; Abd ElHalim, Mohamed Said; Mansour, Salma Yehia (European Journal of Chemistry, 2014)
The reactivity of hydrogen atoms at C-4 of pyrazolone 3 towards condensation reactions was studied by its reaction with p-anisaldehyde, malononitrile and/or ethyl acetoacetate in the presence of ammonium acetate and/or piperidine, glucose, phenyl isothiocyanate, 2-amino thiazole and aniline to afford compounds 4-6, 13, 15, 17 and 18, respectively. Reaction of amino carbonitrile 4 with ammonium thiocyanate, and formamide afforded compound 7 and pyrazolo[3,4-b]pyridinylformamide, 9. Reaction of compound 7 with hydrazine hydrate gave thiocyanato-1,3,4-thiadiazol-2-yl)-1H-pyrazolo[3,4-b]pyridin-6-amine derivative, 8. Acetylation of amino carbonitriles 4 and 5 afforded compound 10 and 11, respectively. Reaction of compound 11 with hydrazine hydrate afforded azanediyl compound 12. The pyrazolone 19 reacted with different nitrogen nucleophiles such as hydrazine hydrate, urea, thiourea and hydroxylamine hydrochloride to afford compounds 22-25. The reactivity of pyrazolone 19 as an α,β-unsaturated compound towards several carbon nucleophiles under Michael reaction was studied by its reaction with ethyl acetoacetate, ethyl cyanoacetate, and malononitrile under different reaction conditions and pyrazolone 3 to afford compounds 26-32, respectively. Synthesis of amino carbonitriles 5, pyrazolone 19 and pyrazolo[3,4-c]pyrazole 22 were carried out under microwave irradiation. The newly synthesized compounds were characterized by IR, 1H NMR and mass spectral data.